On dynamical behavior for optical solitons sustained by the perturbed Chen-Lee-Liu model - Tarla, Sibel; Ali, Karmina K.; Yilmazer, Resat; Osman, M. S. (Iop Publishing Ltd, 2022)
This study investigates the perturbed Chen-Lee-Liu model that represents the propagation of an optical pulse in plasma and optical fiber. The generalized exponential rational function method is used for this purpose. As a result, we obtain some non-trivial solutions such as the optical singular, periodic, hyperbolic, exponential, trigonometric soliton solutions. We aim to express the pulse propagation of the generated solutions, by taking specific values for the free parameters existed in the obtained solutions. The obtained results show that the generalized exponential rational function technique is applicable, simple and effective to get the solutions of nonlinear engineering and physical problems. Moreover, the acquired solutions display rich dynamical evolutions that are important in practical applications.
Keywords: perturbed Chen-Lee-Liu model; generalized exponential rational function method; analytical solutions